Influence of CO2 Partial Pressure on Ethanol Dry Reforming Using 5%Ce-10%Co/Al2O3 Catalyst for Hydrogen Production - Fayaz, Fahim; Ahmad Ziad, Sulaiman; Singh, Sharanjit; Akbari, Sweeta (Universiti Malaysia Pahang, 2016)
The influence of CO2 partial pressure on ethanol dry reforming has been studied over Ce-promoted Co catalyst supported on Al2O3 from 20 to 50 kPa, C2H5OH was kept at 20 kPa and under atmospheric pressure. The catalyst was synthesized using wet impregnation method and tested in a quartz fixed-bed reactor. X-ray diffraction analysis indicated the formation of CeO2, Co3O4 and spinel CoAl2O4 phases on catalyst surface. CoO and Co3O4 and CeO2 phases were formed during temperature–programmed calcination and 5%Ce-10%Co/Al2O3 catalyst has a total high surface area of 137.35 m2 g-1. Both C2H5OH and CO2 conversions was improved with increasing CO2 partial pressure from 20 at 50 kPa and an optimal selectivity of H2 and CO was obtained at 50 kPa.